The significance of thermomechanical processing on the cellular response of biomedical Co–Cr–Mo alloys. (September 2022) - Mori, Manami; Guo, Ting; Yamanaka, Kenta; Wang, Zuyong; Yoshida, Kazuo; Onuki, Yusuke; Sato, Shigeo; Chiba, Akihiko; Misra, R.D.K.
Abstract: Strengthening of biomedical Co–Cr–Mo alloys has been explored via thermomechanical processing for enhancing the durability of their biomedical applications. However, the effects of cold and hot deformation on the cellular activity continue to be unclear. In this study, we prepared Co–Cr–Mo alloy rods via cold swaging and hot-caliber rolling and studied the relationship between the microstructure and cellular response of pre-osteoblasts. The cold-swaged rod experienced strain-induced martensitic transformation, which increased the volume fraction of the hexagonal close-packed (hcp) ε-martensite to ∼60 vol.% with an increase in area reduction ( r ) to 30%. The 111 γ fiber texture of the face-centered cubic (fcc) γ-matrix followed the Shoji−Nishiyama orientation relationship with ε-martensite. Cell culture results revealed beneficial effects of cold swaging on the cell response, in terms of adhesion, proliferation and morphology of cells, although increasing r did not significantly affect cellular metabolism levels. The addition of small content of Zr (0.04 wt.%) led to enhanced focal adhesion of cells, which became more significant at higher r . The microstructural evolution during hot-caliber rolling, namely, grain refinement without any phase transformation and strong texture development, did not appreciably affect the cellular activity. These findings are envisaged to facilitate alloy design and microstructural optimization for favorable tuning the osseointegration of biomedical Co–Cr–Mo alloys.